Анохіна Т. О. Лакуни праформ: лінгвоетимологічна розвідка - Анохіна Т. О. (Philological Treatises, 2020)
The article discusses the origins of linguistic etymological lacunary units in the Ukrainian and English languages. The study focuses on the etymological origins, extinct or old-fashioned words and reconstruction methods. The analysis was performed within the units presupposed of the IndoEuropean origin.